Hubungan Tingkat Stres Dengan Grading Akne Vulgaris Pada Siswi Asrama Assalaam Surakarta - Nuraini, Iin Nila, dr. Flora Ramona S.P, M.Kes.,Sp.KK (2017)
Background : Acne vulgaris is a chronic obstructive inflamatory skin disease of pilosebaceus gland and it is often occured in adolescence, but it can be early in women of 14-17 years old. There are so many etiologic factors that cause acne vulgaris and stress is one of the trigers of acne vulgaris. Stress can increase androgen hormone that cause increase sebum production and stimulate keratinocyte cell and cause of acne vulgaris. Purpose : The purpose of this study is to know the relationship between stress level and grading of acne vulgaris in student's dormitory of Assalam Surakarta. Method : Uses analytic observational method with cross sectional. Spearman correlation test is performed to know significance correlation of two variables. This study uses measuring instrument such as DASS questionnaire and physical diagnosis by a general practitioners. Result : It is found that 100% of 50 student's were suffered from stress and all student had acne vulgaris with mild, moderate and severity grade. The results of the analysis of Spearman correlation were p>0,737. Conclusion : There is no significant correlation beetwen stress level and acne vulgaris garding among female students in Assalam Surakarta boarding school Key words : acne vulgaris, stress, student dormitory